Taller de análisis multiactoral para la promoción del uso sostenible del amaranto: Memorias del taller realizado en Sucre, Bolivia, 19-20 de noviembre de 2009 - Polar, Vivian; Rojas, W.; Jäger, M.; Padulosi, S.; Fundación PROINPA; Bioversity International (2010)
Proceedings of a national workshop held in Sucre, Bolivia, on 19-20 November 2009 to launch a multi-stakeholder collaborative platform for the promotion of the sustainable conservation and use of amaranth in Bolivia. Workshop organized by the ‘Chuquisaca Agency for the Promotion of Amaranth’, PROINPA and Bioversity International in the framework of an international UN Programme supported by IFAD (‘IFAD NUS II Project’) . The publication provides a very useful analysis of challenges and opportunities across the value chain of amaranth in Bolivia along with recommendations to each stakeholder groups on urgent actions needed for addressing a more effective conservation and sustainable use of this crop in the country. A collaborative platform links producer associations, research institutes, researchers, development agencies, civil society, the business sector and policy makers, promoting linkages, building synergies and cooperation along the value chain and can advocate for political support for promoting greater use of Andean grains. This approach shifts from the ‘traditional’ top-down approach, linking research to farmers through extension services, to a new paradigm, involving rural and agricultural innovation systems which link public and private sectors with farmers, civil society organizations and the scientific community. Thus the concept of “innovation” encompasses not only the “technological innovation” itself, i.e. the diffusion of new products and services of a technological nature into the economy, but it includes equally non-technological forms of innovation, such as institutional and organizational innovations.By bringing together all the different stakeholders into a single platform, interactions between producers, local authorities, NGOs, extension agents, service providers, researchers, and buyers are facilitated. In this context each stakeholder brings his/her particular expertise to the table and each of his/her contributions supports the overall implementation of the value chain vision. Ultimately, this collective action is meant to improve the prospects of small farmers in agricultural markets.The document highly recommended for all Agencies and workers engaged in promoting amaranth in Bolivia and other countries in Latin America where this crop is being increasingly recognized as strategic livelihood asset for fighting poverty and nutrition insecurity within a climate changing scenario